Integration and application of business graduate and business leader competency-models - Harper, Donta S., 1974- (Advances in human resources management and organizational development (AHRMOD) book series., 2021)
"This book discusses how to identify the right competencies to meet the organizational need for recruitment, development, and success through scalable approaches at the organizational levels. There will be the identification of technological advancement and value to competency-based modeling paired with the identification of practical ways integration competency-based models gives a competitive advantage"--